“Abyalense” poetics in Central America: a proposal for a literary analysis in the context of digital magazines (Part I) - Arroyo Carvajal, Yordan (2023)
This research makes a proposal for a literary analysis of what is referred to here as the “abyalense poetics in Central America”,from the context of digital magazines. The study considers four digital magazines, New York Poetry Review, Ajkö Ki, Círculo de Poesía, and Altazor, and two poets per region. The cases of Nicaragua, Belize and Honduras are pending for the second part. In total there are sixty poems by authors from Costa Rica (Leonardo Porras Cabrera and Mariana Bejarano), Guatemala (Miguel Ángel Oxlaj Cúmez and Rosa Chávez), El Salvador (Guadalupe Estrada and Paula López), and Panama (Aiban Wagua and Arysteides Turpana). Categories such as indigenous, ladino and indigenist poetry and literary polysystem are developed and considered. As part of the results, different phenomena and aesthetic proposals are mentioned, among them, related to cases of linguistic hybridization, bilingualism, monolingualism, cosmovisions, ethnic resistance, and denunciation. It also opens the space for new proposals on this subject, exposes the lack of an anthology of contemporary Central American Abyalense poetics and presents some limitations of interest for future works.